2020
DOI: 10.1038/s41598-020-74059-z
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of expression, epigenetic, and genetic changes of HNF1B in 130 kidney tumours

Abstract: Hepatocyte nuclear factor 1 beta (HNF1B) is a transcription factor which plays a crucial role in nephronogenesis, and its germline mutations have been associated with kidney developmental disorders. However, the effects of HNF1B somatic exonic mutations and its role in the pathogenesis of kidney tumours has not yet been elucidated. Depending on the type of the tumour HNF1B may act as a tumour suppressor or oncogene, although the exact mechanism by which HNF1B participates in the process of cancerogenesis is un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Although the significance of HNF1B in tumorigenesis has recently been closely analysed and discussed, its exact role and mechanism of action have not yet been fully clarified. There are studies suggesting that HNF1B may act as an oncogene in specific cancer types, such as ovarian clear cell carcinoma 5 , 6 , 21 and papillary renal cell carcinoma 16 . Other studies suggested that HNF1B acts mainly as a tumour suppressor in colorectal, prostate, ovarian, and some other types of solid tumours 3 , 15 , 17 , 18 , 22 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the significance of HNF1B in tumorigenesis has recently been closely analysed and discussed, its exact role and mechanism of action have not yet been fully clarified. There are studies suggesting that HNF1B may act as an oncogene in specific cancer types, such as ovarian clear cell carcinoma 5 , 6 , 21 and papillary renal cell carcinoma 16 . Other studies suggested that HNF1B acts mainly as a tumour suppressor in colorectal, prostate, ovarian, and some other types of solid tumours 3 , 15 , 17 , 18 , 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Our previous work showed a loss of the HNF1B protein expression in several solid tumours, and thus suggests that HNF1B may act in a tumour suppressive fashion in colorectal carcinoma (CRC) 15 , clear cell renal carcinoma (ccRCC) and chromophobe renal cell carcinoma 16 , prostate carcinoma (PC) 17 , and high-grade serous carcinoma (HGSC) 18 . The HNF1B gene promoter methylation (as a typical factor leading to a loss of protein expression) was observed in 55% PC and 38% HGSC samples.…”
Section: Introductionmentioning
confidence: 99%
“…Focusing on kidney neoplastic disease, the development of kidney tumors in the context of HNF1B deficiency syndrome (with or without underlying kidney disease) was rarely observed and reported [48][49][50]. In contrast, the expression of HNF1B per se in kidney tumors has been widely explored and its immunohistochemical evaluation was proposed to differentiate renal oncocytoma (diffusely and strongly positive, nuclear stain) from chromophobe renal cell carcinoma (negative) [51][52][53][54][55].…”
Section: Histopathology Of Neoplastic Conditionsmentioning
confidence: 99%
“…In contrast, the expression of HNF1B per se in kidney tumors has been widely explored and its immunohistochemical evaluation was proposed to differentiate renal oncocytoma (diffusely and strongly positive, nuclear stain) from chromophobe renal cell carcinoma (negative) [51][52][53][54][55]. In clear cell renal cell carcinoma, downregulation of HNF1B was mainly observed, and its loss was associated with high-grade tumor and metastatic disease, suggesting both tumor-suppressive functions and prognostic potential [43,49], as also shown in Wilms tumor [56,57]. Conversely, papillary renal cell carcinoma, mucinous tubular spindle cell carcinoma, and metanephric adenoma were characterized by HNF1B overexpression, supporting its role as a proto-oncogene [58,59].…”
Section: Histopathology Of Neoplastic Conditionsmentioning
confidence: 99%